Visitors Handicraft Buying Patterns Throughout The Sarawak Regatta - Shaik Azahar, Bin Shaik Hussain; Marcini, Ramlie; Febbie, Ruth (2019)
This research is about the handicraft buying patterns of visitors throughout the Sarawak Regatta. The research was carried out by focusing on three objectives which is to identify visitors’ perceptions of handicrafts; to study the factors that influence visitors’ making decisions when buying handicrafts; and to analyze visitors’ perceptions of handicraft sold throughout the Sarawak Regatta. The research method used for this study is quantitative, where questionairres were distributed to visitors at Waterfront, Kuching. Results from data collected and analyzed have shown that the handicrafts’ motifs or patterns sold during the Sarawak Regatta attracted visitors to buy them. In conclusion, this study will help handicraft entrepreneurs and future researchers as their reference.